The Dividend Tax Effect on Share Price on Companies in Indonesia Stock Exchange - Ely Kartikaningdyah; Dudi Aditya (Journal of Applied Accounting and Taxation, 2018)
The purpose of this research is to analyze the effect of tax dividend on share price. The research was conducted for non-financial firms on Kompas 100 category listed on the Indonesia Stock Exchange period 2007 to 2014. In this research share price is measured by price earning ratio, tax dividend by tax rate on Indonesia Tax Law, and dividend policy by dividend payout ratio. Analysis of panel data with random effect model was used to analyze the influence of independent variable and the dependent variable. The result of this study indicate that the tax dividend has an effects to the share price with controlled by dividend policy.